ANALISIS PRILAKU AKUNTANSI ATAS AKUISISI INTERNAL TERHADAP KINERJA KEUANGAN PADA PT.CIPTA NIAGA SEMESTA - H. Andi Rustam (AkMen JURNAL ILMIAH, 2017)
This study aimed to analyze the behavior of the accounting for the acquisition of internal Against financial performance at PT. Cipta Niaga Universe In this method the author uses descriptive method This method is done to obtain information about the current state and see the fit between the financial statements to analyze and forth type of data used is the type primary and secondary data as well as using quantitative and qualitative data. In measuring the performance of companies in the financial statements using a number of methods which is a tool to compare one thing with another thing The method used is the ratio likuiliditas , ratio leverage ratio activity ratio profitability ratios and the ratio of the market with the ratio we can see a comparison of annual financial statements. Acquisitions had a positive impact on the company performance at PT . Cipta Niaga Universe competition turnover outside influence the performance of the company if the goods under go acquisition the old stuff still on sale until stock runs out and the substitute goods sold with FIFO and accountability of the answer in the form of sales reports per items.